2019
DOI: 10.1021/acs.est.8b05019
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot-Scale Field Study: In Situ Treatment of PCB-Impacted Sediments with Bioamended Activated Carbon

Abstract: A combined approach involving microbial bioaugmentation and enhanced sorption was demonstrated to be effective for in situ treatment of polychlorinated biphenyls (PCBs). A pilot study was conducted for 409 days on PCB impacted sediments in four 400 m 2 plots located in a watershed drainage pond in Quantico, VA. Treatments with activated carbon (AC) agglomerate bioamended with PCB dechlorinating and oxidizing bacteria decreased the PCB concentration in the top 7.5 cm by up to 52% and the aqueous concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
3
37
1
Order By: Relevance
“…The need for cost-effective remediation of sites impacted with chlorinated contaminants was a driver leading to the discovery of Dehalococcoidia capable of utilizing chlorinated organic compounds as respiratory electron acceptors (33,34). The organohalide respiration process revolutionized bioremediation at sites impacted with chlorinated pollutants (35,36), and detailed characterization work transformed our understanding of the physiology, biochemistry, and evolution of organohalide-respiring Dehalococcoidia (11). What is generally not acknowledged is that most organochlorines are not only xenobiotics (i.e., anthropogenic chemicals) but also have natural origins.…”
Section: Roles Of Dehalococcoidia In Contaminated and Pristine Enviromentioning
confidence: 99%
“…The need for cost-effective remediation of sites impacted with chlorinated contaminants was a driver leading to the discovery of Dehalococcoidia capable of utilizing chlorinated organic compounds as respiratory electron acceptors (33,34). The organohalide respiration process revolutionized bioremediation at sites impacted with chlorinated pollutants (35,36), and detailed characterization work transformed our understanding of the physiology, biochemistry, and evolution of organohalide-respiring Dehalococcoidia (11). What is generally not acknowledged is that most organochlorines are not only xenobiotics (i.e., anthropogenic chemicals) but also have natural origins.…”
Section: Roles Of Dehalococcoidia In Contaminated and Pristine Enviromentioning
confidence: 99%
“…Thermally altered plant biomass (char) is ubiquitous in the environment and has long been recognized as an important geosorbent for organic compounds and inorganic species, including pollutants. More recent work has revealed that chars are also redox-active by accepting and donating electrons and, thereby, participate in biogeochemical electron transfer processes and pollutant redox transformations. Chars accept electrons from anaerobic microbial respiration or from inorganic reductants in the environment (e.g., hydrogen sulfide). ,,,, ,,,, Following reduction, chars may then transfer electrons to both organic and inorganic pollutants, thereby facilitating their reductive transformation. ,, ,,,, Chars are also involved in electron transfer between microbial cells , or from metal-reducing bacteria to hematite or ferrihydrite. , In addition, electron transfer to and from chars was shown to mitigate emissions of the radiatively active trace gas N 2 O from agricultural soils. , The important role of chars in redox reactions has led to considerable interest in characterizing the redox chemistry and reactivity of chars. However, chars also release dissolved organic carbon (DOC), which herein we refer to as pyrogenic dissolved organic matter (pyDOM) (operationally defined as DOC from bulk chars that passes through 0.45 μm filters). The released amounts of pyDOM are considered significant in the global carbon cycle: for instance, pyDOM is estimated to contribute ∼10% of the riverine flux of DOC to the oceans. , Yet, compared to bulk chars and non-pyrogenic DOM, only a few studies have characterized ...…”
Section: Introductionmentioning
confidence: 99%
“…Amplicon sequencing results were processed using Qiime2-2019.4 [ 27 ] by following the “Atacama soil microbiome” tutorial in https://qiime2.org and a previously published pipeline [ 28 ] in order to create operational taxonomic unit (OTU) tables. A median of 20 quality score was used as threshold to truncate low-quality nucleotides.…”
Section: Methodsmentioning
confidence: 99%